Health literacy of primiparae in the first six months of maternity: review - Katarína Žiaková; Juraj Čáp; Michaela Miertová; Elena Gurková (University of Ostrava, 2019)
Aim: The aim was to synthesize themes and influencing factors of personal dignity experienced among patients with multiple sclerosis (MS) in the context of health care. Design: A qualitative narrative review with regard to PRISMA statements was used as a study design. Methods: The CASP Qualitative checklist was chosen for critical appraisal and thematic synthesis for synthesis of findings was adopted. Narrative the electronic databases: Academic Search Complete; Health Source: Nursing/Academic Edition; Humanities International Complete; MEDLINE were used for search. 230 studies were retrieved. 4 studies met the reviewers' inclusion criteria and were included into the study. Results: Three synthesized themes - Ill body, changed healthy identity and personal integrity (8 subthemes); Fighting spirit and patient's factors (8 subthemes) and Social factors (8 subthemes) - seem to be relevant for dignity of patients with MS. Narrative review shows tendency that patients with MS are in the danger of loss of dignity. Conclusion: Focused on personal dignity of people with MS brings possibility to have non-psychiatric approach to patients' personality fully consistent with the patient-centred approach in the context of health care. Results will be used as a framework for ethical reflection, interventions focused on how to improve or maintain personal dignity of patients with MS. Based on the critical appraisal, researchers should pay more attention to reflexivity. According to study limitations, a systematic review is needed.